Resistance of cotton genotypes to silverleaf whitefly (Bemisia tabaci [GENNADIUS] Biotype B) - Silva Oliveira, Carlos Eduardo da [UNESP]; Hoffmann, Lucia Vieira; Toscano, Luciana Claudia; Queiroz, Mariana Silva; Zoz, Tiago; Witt, Travis Wilson (Springer, 2020)
Silverleaf whitefly (Bemisia tabaci biotype B) has caused significant damage, year after year, and can be considered one of the major pests responsible for the increase in use of insecticides in cotton. This research aimed to evaluate the biology and preference for oviposition and feeding of Bemisia tabaci biotype B in wild cotton genotypes. The experiments were conducted at the Experimental Farm of the Mato Grosso do Sul State University, Cassilandia-MS, from March 24th to May 13th, 2017. The treatments were composed of the following genotypes:, APGO 01 and APGO 02 (Gossypium barbadense),TEX 1116 and TEX 1964 (G. hirsutum) and G. arboreum acquired in EMBRAPA germplasm, BRS 269 (standard cultivar/control) widely grown in Brazil. The infestations were carried out on plants 25 days after emergence in a no-choice test and at 42 days for the free-choice test, the cages they were infested with 100 whitefly adults per plant. The number of eggs per leaf, the density of trichomes, the viability of nymphs and the duration of the juvenile phases, in days, on the youngest leaf in the upper third of the plant were evaluated. The averages for cotton genotypes were grouped by the Scott Knott test at the 5% probability level. Low preference for oviposition of B. tabaci biotype B on genotypes APGO 01 and APGO 02 was observed in the no-choice test. The genotypes APGO 01, APGO 02, and BRS 269 were the least preferred for oviposition and had the lowest density of trichomes at 43 days after emergence in 24 hours after infestation. It was verified that in the genotypes APGO 01 and APGO 02, there was an increase in the density of trichomes, and consequently, there was an increase in the number of eggs per cm(2) in 48 hours after infestation. After 72 hours of infestation, a positive and significant correlation (r = 0687**) was observed between the number of eggs per cm(2) and the density of trichomes. A positive correlation was observed between the density of trichomes and the preference of oviposition. A negative effect of glandular trichomes and preference for oviposition was observed for APGO 02.. Resistance by antibiosis and / or non-preference for feeding in the genotypes APGO 01, APGO 02 and G. arboreum were observed for prolonging the development of the insect in the juvenile/nymph phase.
Keywords: Silverleaf whitefly; Cotton germplasm; Resistance to insects; Antibiosis; Glandular trichomes